The Impact Of The Covid-19 Pandemic On The International Сompetitiveness Of Multinational Enterprises - Mariya KHMELYARCHUK; Svitlana LASZKEVYCH (Communications of International Proceedings, 2021)
The article is devoted to the impact of the COVID-19 pandemic on the international competitiveness of international enterprises, their competitive advantages and competitive potential. The authors analyzed the successful strategies of multinational corporations, which occupy leading positions in international markets and have demonstrated high resilience to crisis processes. It is determined that high competitiveness was demonstrated by multinational corporations, whose activities meet the requirements of the time and are carried out in accordance with modern trends of digitalization, greening and sustainability of all spheres of socio-economic processes. The research showed a generally negative impact of the pandemic on international investments, presenting a decline in almost all regions of the world.  At the same, time multinational corporations showed their rapid readiness to increase investments in the face of a slowing pandemic and the availability of a favorable investment environment, which is provided by broad state and international support for international investments. According to the authors, such support is extremely necessary and urgent, as it is known, that the inflow of investment into the economy is the important mechanism to stimulate economic activity and post-crisis economic recovery.
Keywords: international competitiveness; multinational corporations; pandemic; investments.